Multidrug-resistant Candida auris: 'new kid on the block' in hospital-associated infections?. Issue 3 (November 2016) - Chowdhary, A.; Voss, A.; Meis, J.F.
Summary: Since being first reported in an ear swab in 2009, and in blood cultures in 2011, invasive infections with Candida auris have been reported in many countries across several continents. We review current knowledge of the epidemiology of this emerging multidrug-resistant pathogen. The importance of species identification and the inadequacies of many widely used identification systems are considered. We recommend that hospitals develop their own policies for the prevention and control of infections with this pathogen. Elements of such policies and the limitations of the existing knowledge base are discussed.